Genetic Profiling of CYP19 Gene Haplotype in Holstein Bulls - Hassan Nima Habib; Khalaf A.H.Al-Rishdy; Murthda F.AL-Hellou (Institute of Medico-legal Publications Pvt Ltd, 2021)
The CYP19 gene is a protein-coding gene that stimulates the transmutation of androgens to estrogens,aromatase activity is related to haplotypes of the CYP19 gene, therefore this study aimed to detect haplotypesof the CYP19 gene in the Holstein bulls. This study, conducted from October 2018 to June 2019. Forty-twoBulls, aged between 4-6 years old were used, which belonged to local farmers in Basra city, south of Iraq.The DNA was extracted from semen, PCR amplification was carried out to acquire the DNA sequence. Thesequences were analyzed by using some Bioinformatics tools. The results showed four haplotypes in theCYP19 gene as a result of silent and missense mutations in comparison with the same gene in GenBank, allthe haplotypes are recorded in GenBank, DDBJ and EMBL. These findings call for further studies to revealthe relationship of CYP19 gene haplotypes and semen characteristics to uncover bulls’ fertility